2011
DOI: 10.4103/0256-4947.75790
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cervical cord and medulla in posterior reversible encephalopathy syndrome

Abstract: The posterior reversible encephalopathy syndrome (PRES) is characterized by patchy cortical and subcortical lesions in the distribution of the posterior circulation. The lesions are classically reversible. This syndrome has multiple etiologies, most of which cause acute hypertension. We present a case of PRES with involvement of the medulla and cervical cord (apart from the typical parieto-occipital lesions)-an extremely rare imaging manifestation of PRES. It is important to recognize the imaging findings of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…16 On the other hand, Fugate et al demonstrated in a large clinical series (113 patients) that cerebellar involvement was significantly more frequent in patients with a history of autoimmunity compared with those without autoimmunity. 23 Nine cases of spinal cord involvement are reported in the literature [33][34][35][36][37][38][39] . All patients had confluent expansile central spinal cord T2 hyperintensity spanning at least 4 spinal segments, originating at the cervicomedullary junction.…”
Section: Distributionmentioning
confidence: 97%
“…16 On the other hand, Fugate et al demonstrated in a large clinical series (113 patients) that cerebellar involvement was significantly more frequent in patients with a history of autoimmunity compared with those without autoimmunity. 23 Nine cases of spinal cord involvement are reported in the literature [33][34][35][36][37][38][39] . All patients had confluent expansile central spinal cord T2 hyperintensity spanning at least 4 spinal segments, originating at the cervicomedullary junction.…”
Section: Distributionmentioning
confidence: 97%
“…1,8,13 There are a few cases in literature that report the involvement of the spinal cord in this syndrome. [14][15][16][17][18] The elevation of blood pressure was reported in the cases of spinal cord involvement in PRES. In the case described in this paper, the patient was exposed to many triggers for PRES: elevation of blood pressure, acute renal failure and chemotherapy.…”
Section: Case Reportsmentioning
confidence: 99%
“…In the case described in this paper, the patient was exposed to many triggers for PRES: elevation of blood pressure, acute renal failure and chemotherapy. [14][15][16][17][18] Another interesting topic is that PRES involves predominantly the white matter of the brain, and in the brain stem and spinal cord the lesions described affect the gray matter. Normally, patients with spinal cord lesion had alterations in neurological examination (sensitive and motor deficits).…”
Section: Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The syndrome commonly affects hypertensive patients, but may also occur in normotensive individuals in 20–30% cases. [ 1 2 ] PRES with spinal cord involvement (PRES-SCI) is an extremely rare entity which should be suspected when patients with PRES have neurologic signs clinicoradiologically located to spinal cord with severe hypertension or grade IV hypertensive retinopathy. [ 2 ] We describe PRES-SCI involving the cervical spinal cord in a known case of Henoch-Schönlein purpura (HSP) caused by hypertension and uremia.…”
Section: Introductionmentioning
confidence: 99%